Biomimetic apposition compound eye fabricated using microfluidic-assisted 3D printing - Bo Dai (Nature Portfolio, 2021)
Insect-like biomimetic compound eyes have many technological applications. Here, the authors present a facile fabrication scheme involving microfluidics assisted 3D printing that permits to completely separate design, optimization and construction of optical and sensor components.